EFFECT OF POULTRY DROPPINGS ON WATER QUALITY PARAMETERS IN INDIAN MAJOR CARP PONDS - I. Ahmed; M. Ashraf; S. Abbas; P. Akhtar (Journal of Animal and Plant Sciences, 2013)
The present study was designed to investigate the influence of poultry droppings on the physico-chemical factors in fish ponds during different seasons of the year. There were two treatments and a control and all the groups were replicated. Control pond did not receive any additive while treatment 1 and 2 were manured with poultry droppings at the rate of 0.15 (T1) and 0.20 (T2) g N/100 g wet fish body weight daily. Temperature ranged from 27.7 to 35.7, 28.9 to 35.0 and 28.3 to 35.3oC, light penetration from 10 to 28, 10 to 32 and 10 to 35 cm, pH from 7.50 to 8.17, 7.0 to 8.15 and 7.40 to 8.20, dissolved oxygen from 5.30 to 8.30, 4.49 to 10.89 and 5.53 to 10.65 mg/l, total alkalinity from 220 to 450, 280 to 450 and 290 to 410 mg/l, carbonates from 10 to 40, 10 to 60 and 20 to 60 mg/l, bicarbonates from 200 to 420, 270 to 410 and 270 to 370 mg/l, total hardness from 180 to 280, 200 to 280 and 210 to 280 mg/l, calcium from 30.0 to 72.1, 30.0 to 62.65 and 27.0 to 64.4 mg/l, magnesium from 10.9 to 41.87, 17.1 to 40.0 and 17.3 to 43.7 mg/l, total solids from 814 to 1390, 818 to 1520 and 816 to 1520 mg/l and planktonic biomass from 14 to 290, 18 to 320 and 16 to 320 mg/l in control, T1 and T2 from April to September, respectively. All the parameters remained uniform in all the treatments and a control except plankton productivity which was higher in both treatments when compared with control though there were no differences between both treatments. It further proves that use of 0.15 (T1) or 0.20 (T2) g N/100 g wet fish body weight daily does not make any difference neither it has any deleterious effects on water quality nor any on pond productivity. Therefore lesser quantity is more safe and cost effective for fish pond applications.
Keywords: Physico-chemical parameters; poultry droppings